Life cycle and determination of larval instars of Leucinodes orbonalis guenee (Lepidoptera : Crambidae) - Abdul Baqi Rostaee; Nur Azura Adam; Syari Jamian (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
The eggplant shoot and fruit borer, Leucinodes orbonalis Guenee is a significant and destructive pest of eggplant causing considerable damage to shoot and fruits in South and Southeast Asian countries including Malaysia. Therefore, it is important to understanding the life cycle if this species in order to implement the best management strategy. The objective of this study was to investigate the life cycle L. orbonalis. The result on the biology of L. orbonalis recorded that the incubation period was 5.5±0.09 days; the total larval period was 12.07±0.19 days; and underwent five larval instars stages which are characterized by the size of the cephalic capsule. The pupal stage took 10.37±0.10 days. The mean lifespan of adult females and males moths were recorded at 4.75±0.17 days and 3.4±0.23 days respectively. The duration of the total life cycle of the females and males moths were 32.67±0.55 days and 31.32±0.61 days respectively. On average, each female produced 174±22.01 eggs with the sex ratio of female to male was almost 2:1. The eggs were measured at 0.66±0.01 mm in length and 0.31 ±0.01 mm in width. The full-grown larvae were measured at 15.49±0.50 mm body length and 1.37±0.04 mm head capsule. Pupae were measured at 7.79±0.25 mm in length with 2.49±0.07 mm body width, females were on average of 9.63±0.24 mm in length with 21.41±0.35 mm wing width whereas the mean value for male was measured 7.43±0.13 mm body length with 16.28±0.36 mm wing width. Result of this research may be helpful to develop an effective pest management strategy.